Eternal Distance On the Significance of Window- and Cave Representations in Northern Romanticism - Somhegyi, Zoltán (The Nordic Journal of Aesthetics, 2016)
Romanticism was the first period in art history that explicitly started to question the possibilities of a direct understanding of Nature and of achieving concrete and exact knowledge of it or of the “outside” world. In many cases, it can even be interpreted as a direct counter-tendency to the Enlightenment¢•s concept of domestication and domination of Nature. In this paper it is argued that many window- and cave representations of Romanticism, especially in Northern Romanticism, are strongly connected with the differentiation of inside and outside, thus the main affirmation and message of these pictures is the inaccessibility of Nature, and this influences the composition, appearance and interpretation of the works.